Evaluation of the immunogenicity and protective efficacy of a recombinant CS6-based ETEC vaccine in an Aotus nancymaae CS6 + ETEC challenge model. Issue 3 (15th January 2021) - Ramakrishnan, A.; Joseph, S.S.; Reynolds, N.D.; Poncet, D.; Maciel, M.; Nunez, G.; Espinoza, N.; Nieto, M.; Castillo, R.; Royal, J.M.; Poole, S.; McVeigh, A.; et al.
Abstract: Colonization factors or Coli surface antigens (CFs or CS) are important virulence factors of Enterotoxigenic E. coli (ETEC) that mediate intestinal colonization and accordingly are targets of vaccine development efforts. CS6 is a highly prevalent CF associated with symptomatic ETEC infection both in endemic populations and amongst travelers. In this study, we used an Aotus nancymaae non-human primate ETEC challenge model with a CS6 + ETEC strain, B7A, to test the immunogenicity and protective efficacy (PE) of a recombinant CS6-based subunit vaccine. Specifically, we determined the ability of dscCssBA, the donor strand complemented recombinant stabilized fusion of the two subunits of the CS6 fimbriae, CssA and CssB, to elicit protection against CS6 + ETEC mediated diarrhea when given intradermally (ID) with the genetically attenuated double mutant heat-labile enterotoxin LT(R192G/L211A) (dmLT). ID vaccination with dscCssBA + dmLT induced strong serum antibody responses against CS6 and LT. Importantly, vaccination with dscCssBA + dmLT resulted in no observed diarrheal disease (PE = 100%, p = 0.03) following B7A challenge as compared to PBS immunized animals, with an attack rate of 62.5%. These data demonstrate the potential role that CS6 may play in ETEC infection and that recombinant dscCssBA antigen can provide protection against challenge with the homologous CS6 + ETEC strain, B7A, in the Aotus nancymaae diarrheal challenge model. Combined, these data indicate that CS6, and more specifically, a recombinant engineered derivative should be considered for further clinical development.